IMPACT OF PRODUCT QUALITY, PRICE CHOICES, AND DIGITAL PUBLICITY ON THE DECISIONS TO BUY TOMORO COFFEE ON BEKASI CITY - Dewi Puspaningtyas Faeni; Muhammad Farhan Raziq (Cahaya Ilmu Bangsa, 2024)
This study attempts to examine how consumer purchasing decisions at Tomoro Coffee in Bekasi are influenced by price selection, product quality, and digital publicity. A questionnaire with 100 respondents who were Tomoro Coffee customers in Bekasi was used to gather the data. Double linear regression was employed in the data analysis process. The study's findings demonstrate that, at Tomoro Coffee in Bekasi, customer purchase decisions are positively and significantly influenced by product quality, pricing strategy, and digital exposure. Consumer purchasing decisions are primarily influenced by product quality, with price selection and digital advertising coming in second and third. The findings of this study have significant ramifications for coffee businesses in terms of their ability to comprehend consumer purchase behavior and create more successful marketing campaigns. Additionally, It can also serve as a resource for other academics that are looking into the variables influencing customer decisions to purchase coffee.